Coating Properties of UV Curable Coatings on Natural Nails: Impact Evaluation of 5 Different Acrylate Monomers - Zane GRIGALE-SOROCINA; Ingmars BIRKS; Estefanija BOGDANOVA (Medžiagotyra, 2022)
Compositions on natural nails mostly contain acrylic monomers, more often 2-hydroxyethyl methacrylate (HEMA). These systems have been considered to be a potent sensitizer in contact with the skin. The purpose of the study was to compare five acrylic monomers: HEMA (hydroxyethyl methacrylate), HPMA (hydroxypropyl methacrylate), IBOMA (isobornyl methacrylate), MEP (methacryloylethylphosphate) and TMPTMA (trimethylpropane trimethacrylate) to find the substitute to HEMA. In this study, we explored the rheological and polymerization properties of uncured systems containing five acrylate monomers. Mechanical and adhesion properties were evaluated of cured compositions. Optimal criteria of compositions and cured coatings were defined, and tests were performed to find the most appropriate composition. HEMA is the most widely used acrylic monomer in nail coatings due to its outstanding characteristics: high reactivity (temperature reached at polymerization Tmax = 95 °C), good adhesion (1.5 MPa on glass and aluminum), high solubility in acetone (ms = 22 %). The greatest potential to substitute HEMA has monomer HPMA, due to its good abrasion resistance (G = 66 GU after abrasion), high reactivity (Tmax = 88 °C), and adhesion (1.5 MPa on glass and on aluminum). The polymerization process of a composition containing MEP was the fastest and reached the highest maximum temperature during polymerization process (Tmax = 115 °C) and great adhesion (2.5 MPa). The best surface abrasion resistance (G = 76 GU after abrasion) was reached for coatings containing TMPTMA.